2019
DOI: 10.1097/gox.0000000000002086
|View full text |Cite
|
Sign up to set email alerts
|

Ultra High-frequency Ultrasonographic Imaging with 70 MHz Scanner for Visualization of the Lymphatic Vessels

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
81
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 100 publications
(83 citation statements)
references
References 30 publications
1
81
0
1
Order By: Relevance
“…The target lymphatic vessels were visible with high contrast against the background and could be clearly differentiated from blood vessels due to spectral absorption differences between hemoglobin and indocyanine green. As previously described [16], this differentiation can be confirmed by gently pressing the 3D probe against the skin: the image of only the vein, not the lymphatic, will disappear, to reappear when pressure is lifted. Although we could also evaluate lymphatic patency by ultra-high frequency ultrasound [16], this technique is limited to a depth of 1 cm, which precludes application in more proximal segments of an affected limb and in advanced stages of lymphedema.…”
Section: Msot Differentiates Between Distinct Types Of Vessels Includsupporting
confidence: 52%
“…The target lymphatic vessels were visible with high contrast against the background and could be clearly differentiated from blood vessels due to spectral absorption differences between hemoglobin and indocyanine green. As previously described [16], this differentiation can be confirmed by gently pressing the 3D probe against the skin: the image of only the vein, not the lymphatic, will disappear, to reappear when pressure is lifted. Although we could also evaluate lymphatic patency by ultra-high frequency ultrasound [16], this technique is limited to a depth of 1 cm, which precludes application in more proximal segments of an affected limb and in advanced stages of lymphedema.…”
Section: Msot Differentiates Between Distinct Types Of Vessels Includsupporting
confidence: 52%
“…The CDU technology is continuing to evolve, assisting surgeons to visualize very superficial structure with more clarity, elevate thin flaps, and identify lymphatic vessels via high-frequency CDUs. 38,39 Conclusion CDU is a valuable and powerful tool for any reconstructive surgeons who are interested in performing microsurgery or supermicrosurgery. In our systematic review, we found that there are a limited number of literatures on the role of CDU in reconstructive surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Ultra-high frequency ultrasound preoperative planning of the rerouting method for lymphaticovenular anastomosis in incisions devoid of vein Dear Editor, Supermicrosurgical lymphaticovenular anastomosis (LVA) represents a valid surgical option for the treatment of peripheral lymphedema (Scaglioni, Fontein, Arvanitakis, & Giovanoli, 2017). However, the shunts should be performed using still functional lymphatics channels and favorable recipient venules (Hayashi et al, 2019;Visconti, Hayashi, Bianchi, & Salgarello, 2019;Visconti, Salgarello, & Hayashi, 2018;Visconti, Yamamoto, Hayashi, & Hayashi, 2017).…”
mentioning
confidence: 99%
“…(Below, right) The venule was rerouted through a subcutaneous tunnel into the lymphatic incision to perform the LVA. LVA, lymphaticovenular anastomosis venule to use (Hayashi et al, 2019;Visconti et al, 2017Visconti et al, , 2018Visconti et al, , 2019.…”
mentioning
confidence: 99%
See 1 more Smart Citation